Effect of the clarification pH of sorghum juice on the composition of essential nutrients for fermentation - Durán, Marcos Antonio (2018)
The growing demand to replace fossil fuels with renewable alternatives has generated an urgent and imminent global need to find new non-fossil sources. Sweet sorghum is widely recognized as a highly promising biomass energy crop with the particular potential to complement sugarcane for ethanol production. Our aim in this study was to evaluate the influence of pH during the clarification process on the composition of essential nutrients in the sorghum juice and observe how this affects the efficiency of the ethanol fermentation process. We found that a higher pH directly affected residual concentrations of key nutrients (P, Ca, Zn and Mn) and consequently the efficiency of ethanol fermentation. In conclusion, we recommend a clarification procedure at pH 6-6.5 in order not to significantly affect nutritional parameters important for the yeast fermentation process.